Volume replacement in dengue shock syndrome - Wills, B (2001)
The treatment of dengue shock syndrome (DSS) is a medical emergency. Prompt and vigorous volume replacement therapy is required, with extreme care to avoid fluid overload. Recognition of the importance of increased vascular permeability in the pathophysiology of DSS and of the critical need for parenteral fluids in resuscitation has had a dramatic effect on mortality from the disease over the last 40 years. However, until recently there has been little research to determine the optimal fluid regimen, and the choice of fluid has remained largely empirical. Colloid and crystalloid fluid have different physicochemical properties which influence the patterns of distribution and elimination, as well as the secondary osmotic effects. In two recent double-blind randomized trials in Viet Nam, initial resuscitation with colloids fluids (dextran 70 or 3% gelatin) restored cardiac index and pulse pressure and normalized haemotocrit more quickly than either of the crystalloid fluids (physiological saline or Ringer's lactate). There was no difference, however, in the overall recovery time or the subsequent requirement for fluids. From the larger study it was apparent that the major determinant of clinical response was the width of the pulse pressure at presentation with shock, the small number of children with pulse pressures of ≤ 10 mm Hg requiring significantly more resuscitation than those with higher pulse pressures. Within this more compromised group there was a trend to earlier, sustained recovery among those who received one of the colloids. It appears that the majority of children with DSS recover with infusion of crystallois fluids alone, but that an important minority may benefit initial resuscitation with a colloid. Large trials will be necessary to confirm this effect and to clearly characterize the subgroup of children who might benefit from initial colloid therapy. Given the huge burden of dengue disease in South-East Asia, if a true benefit is established in a subgroup of patients, this may have a significant influence on mortality in the region.